Blood Glucose Variations and Clinical Experience with Glibenclamide in Diabetes Mellitus. Issue 5709 (6th June 1970) - O'Sullivan, D. J.; Cashman, W. F.
Abstract : Thirty patients were treated with glibenclamide for periods up to 16 months. The drug is a potent hypoglycaemic agent, and taken in a single daily dose controls blood glucose levels over a 24-hour period in maturity onset diabetes. A definite dose-effect relationship exists, and the drug may be used in doses of 5 to 20 mg. daily. There were no appreciable side-effects or toxic effects during the period of study.